2022
DOI: 10.3389/fmicb.2021.811157
|View full text |Cite
|
Sign up to set email alerts
|

Nipah Virus–Another Threat From the World of Zoonotic Viruses

Abstract: Among the diseases that pose a serious threat to public health, those caused by viruses are of great importance. The Nipah virus (NiV) belonging to the Paramyxoviridae family was reported in Malaysia in 1998/1999. Due to its high mortality in humans, its zoonotic nature, the possibility of human-to-human transmission, and the lack of an available vaccine, the World Health Organization (WHO) has recognized it as a global health problem. Depending on strain specificity, neurological symptoms and severe respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 82 publications
(222 reference statements)
0
41
0
Order By: Relevance
“…This may be due to the natural progression of the technology life cycle or external factors such as regulations on probiotics research. Either way, in light of the COVID-19 pandemic and any future infectious disease outbreaks caused by our changing society ( Hersh et al, 2012 ; Zhang D. et al, 2021 ; Skowron et al, 2022 ), it is important to stimulate the progression of the state of the art of clinical modalities targeting infectious diseases. As highlighted before ( Larsen and van de Burgwal, 2021 ), such progression should consider the effect of changes to microbial communities across ecosystems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the natural progression of the technology life cycle or external factors such as regulations on probiotics research. Either way, in light of the COVID-19 pandemic and any future infectious disease outbreaks caused by our changing society ( Hersh et al, 2012 ; Zhang D. et al, 2021 ; Skowron et al, 2022 ), it is important to stimulate the progression of the state of the art of clinical modalities targeting infectious diseases. As highlighted before ( Larsen and van de Burgwal, 2021 ), such progression should consider the effect of changes to microbial communities across ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Even as late as 2019, infectious diseases such as lower respiratory tract infections, diarrheal diseases, and tuberculosis were still in the top 10 global causes of death and/or disability-adjusted life years (DALYs; Global Health Observatory, 2021 ). Previous outbreaks of severe acute respiratory syndrome (SARS), Middle East respiratory syndrome (MERS), and the current COVID-19 pandemic have demonstrated that zoonotic diseases are on the rise ( Skowron et al, 2022 ). Moreover, the incidence and burden of lower respiratory tract infections are predicted to increase in our aging population, which can have detrimental effects on healthcare systems if the situation remains unchanged ( Feddema et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sequences obtained from Malaysian human cases suggested only one source of human infection from an amplifying porcine host whereas the Bangladesh cases have shown multiple introductions of the virus to humans [ 61 , 62 , 63 ]. Some of the most recent NiV outbreaks have taken place in India in Kerala between 2018 and 2021, one of which exceeded a 90% mortality rate [ 64 , 65 ]. Outbreaks in India have been shown to be caused by NiV strains close to those circulating in Bangladesh [ 65 , 66 ].…”
Section: Generalitiesmentioning
confidence: 99%
“…Some of the most recent NiV outbreaks have taken place in India in Kerala between 2018 and 2021, one of which exceeded a 90% mortality rate [ 64 , 65 ]. Outbreaks in India have been shown to be caused by NiV strains close to those circulating in Bangladesh [ 65 , 66 ]. Altogether, these data have led to the classification of two strains: Malaysian Nipah virus and Bangladesh Nipah virus.…”
Section: Generalitiesmentioning
confidence: 99%
“…Even as late as 2019, infectious diseases such as lower respiratory tract infections, diarrheal diseases, and tuberculosis were still in the top 10 global causes of death and/or disabilityadjusted life years (DALYs;Global Health Observatory, 2021). Previous outbreaks of severe acute respiratory syndrome (SARS), Middle East respiratory syndrome (MERS), and the current COVID-19 pandemic have demonstrated that zoonotic diseases are on the rise (Skowron et al, 2022). Moreover, the incidence and burden of lower respiratory tract infections are predicted to increase in our aging population, which can have detrimental effects on healthcare systems if the situation remains unchanged (Feddema et al, 2021).…”
Section: Introductionmentioning
confidence: 99%